The persuasion of the Sri Lankan audience towards satellite television - K.P. Gamage (My University, 2021)
The medium of communication was created to fulfill the needs of human beings and later developed it into a complicated nature of technology. Television is a positive apparatus to spend their time to enjoy something simple and to obtain entertainment and education. Satellite television is a television system in which the signal is transmitted to an orbiting satellite and transmits the amplified signal back to the earth. It was started on the 27th of May, 2003 by CBN Sat. Company and Sri Lankan audience got a great opportunity to get exposed to digital experience. But, this satellite television system was legally shut down on the 06th of June 2006 on vague allegations of improper license, the broadcasting of fashion TV and LTTE related programs. The Dialog television which was commenced in 2007 could fill this void. At the very outset, there were over 25,000 subscribers and it has increased up to 1, 45,000 immediately. The research problem of this study is what made the audience persuade towards satellite television network when there is an already available terrestrial transmission system. The interviews, Question areas, Content Analyzing and Observation were used for collecting data. Earlier the Analogue system was used for the terrestrial transmission and this leads to form unclear pictures and sounds. Since the digital transmission system was used for the satellite television system the masses could undergo a digital experience. Moreover, the advent of the satellite television system leads to increase the number of viewers, to overcome the geographical boundaries, to overcome the limitations of the range of frequency and the viewers got an excellent opportunity to view more foreign channels.